THE INTERNATIONAL LEGAL STATUS OF THE CASPIAN SEA: GEOPOLITICAL CONSIDERATIONS OF THE CASPIAN STATES AND HYDROCARBON RESOURCES - ZHILTSOV, Sergey (CENTRAL ASIA AND THE CAUCASUS, 2017)
The dissolution of the U.S.S.R. and the subsequent independence of the former Soviet republics (Azerbaijan, Kazakhstan, and Turkmenistan) led to a shift in the geopolitical landscape of the Caspian region. Five new entities emerged on the shores of the Caspian Sea. Almost immediately, the issue of defining the status of the Caspian Sea arose. Historical Russo-Persian and Soviet-Iranian agreements, despite their long history, did not clarify the international legal status of the Caspian Sea or regulate the utilization of its subsoil resources. During the U.S.S.R. era, there was no need to regulate the development of mining in the Caspian region because all the Caspian Soviet republics were governed by a unified legal code. Moreover, unlike in the 19th century, when Caspian oil fields had a significant impact on the world oil market, the 20th century saw a shift in the center of oil production to other regions of the Soviet Union. As a result, interest in the Caspian region and its hydrocarbon resources diminished sharply.